HUBUNGAN POLA ASUH IBU TERHADAP PERKEMBANGAN SOSIAL ANAK PRA SEKOLAH DI KELOMPOK BERMAIN BUNAYYA PEKANBARU TAHUN 2018 - Hamidah Sari Batubara; Rika Sri Wahyuni; Dina Apriani Adha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Preschoolers are an individual development phase of about 2-6 years, some physical development in preschoolers. Parents are the main role takers in nurturing their children. Parenting patterns of parenting are patterns of behavior that parents use to connect with children. The formulation of the problem from this research is